Pengaturan Peran Notaris Sebagai Pejabat Pembuat Akta Koperasi: Analisis Keabsahan Koperasi Sebagai Badan Hukum - Dwijayanti, Kadek; Jayantiari, I Gusti Agung Mas Rwa (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 9 No 03 (2024), 2024)
The power to create cooperative establishment deeds, amendments to cooperative articles of association, and other pertinent cooperative papers lies with the notary public designated to handle cooperative deeds. The aim of this research is to examine and assess the duty of Notaries who make Cooperative Deeds in terms of their authority to make Cooperative Establishment Deeds and the validity of Cooperative Establishment Deeds made by notaries who are not Notaries Making Cooperative Deeds in accordance with Article 3 paragraph (1) of the Minister of Cooperatives and UKM Decree No. 98/Kep/M.KUKM/IX/2004. The benefits of law can be found in the form of legal certainty. The author employed normative legal research methodologies with a statutory perspective. The findings of this paper signify that the function of the Notary who signs the Cooperative Deed in terms of his power to sign the Cooperative Deed of Establishment is to offer legal certainty for the cooperative as a legal entity. Aside from that, the government has not acknowledged the legitimacy of cooperatives as legal organizations founded using the Deed of Establishment of Cooperatives produced without the presence of a Notary Making Cooperative Deed, and their legal power is weak because it conflicts with Kepmenkop and UKM No. 98/Kep/M.KUKM/IX/2004